Land use and technology adoption analysis of paddy (Oryza sativa) cv. Basmati 370 in irrigated sub-tropics of Jammu district - SLATHIA, P S; KUMAR, RAKESH; NAIN, M S; SHARMA, B C; PAUL, NARINDER (The Indian Journal of Agricultural Sciences, 2018)
Basmati rice (Oryza sativa L.) of Jammu district especially Basmati-370 variety is world famous among the different Basmati varieties grown in the region due to its delicious taste, superior aroma and distinct flavour.The present productivity level of rice is far from potential level.Thus in order to ascertain the impact of various cultivation practices adopted by the Basmati growers and different factors affecting its productivity, a research pursuit was undertaken in Jammu district with 120 randomly selected farmers. The study reveals that majority of farmers transplanted their paddy crop in second week of July, only 6% adopted seed treatment practice and none of the farmers adopted seedling treatment, 85% applied DAP after transplanting and urea was the only fertilizer - applied by almost all the growers. Butachlor was applied as pre emergence herbicide by about 65% of the farmers immediately after transplanting and 52 per cent farmers applied bispyric sodium herbicide for the control of post emergence weeds. None of the farmers used any type of pesticides in Basmati 370 in the study area. The average productivity of Basmati 370 paddy cultivar of respondent farmers was to the tune of 2.841 tonnes/ha. Multiple linear regression model so applied shows that use of DAP fertilizer significantly affected the productivity of Basmati 370 variety of paddy. Low use of agro-chemicals in Basmati 370 cultivation, indicate scope for promotion of good agricultural practices (GAPs) or organic cultivation of Basmati 370 for increasing its sustainability both at national as well as international level which may result in appropriate return in addition to environmental benefits.